1995
DOI: 10.1007/bf03010712
|View full text |Cite
|
Sign up to set email alerts
|

Pressure support ventilation with the laryngeal mask airway: a method to manage severe reactive airway disease postoperatively

Abstract: The use of a laryngeal mask airway (LMA) and a bi-level positive airway pressure (BiPAP~) machine is described in a post

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…These results agree with the findings of previous case reports or case series. Groudine et al 13 describe a case where a laryngeal mask airway device was used after DLT extubation to provide positive pressure ventilation in the intensive care unit. In the three cases reported by Sasano et al, 14 a laryngeal mask airway device was found to improve the quality of emergence in patients undergoing lung volume reduction for severe emphysema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results agree with the findings of previous case reports or case series. Groudine et al 13 describe a case where a laryngeal mask airway device was used after DLT extubation to provide positive pressure ventilation in the intensive care unit. In the three cases reported by Sasano et al, 14 a laryngeal mask airway device was found to improve the quality of emergence in patients undergoing lung volume reduction for severe emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…12 This technique has been used in sporadic case reports. [12][13][14] The goal of this study was to compare coughing at extubation in three situations after thoracic surgery was performed with a DLT in place: (1) replacing the DLT with a laryngeal mask airway device; (2) replacing the DLT with a single-lumen ETT; and (3) leaving the DLT in place. The primary outcome was the number of coughing episodes, and secondary outcomes were the number of subjects with no coughing episodes and side effects.…”
mentioning
confidence: 99%
“…Other ventilation modalities, such as positive pressure in the airways (BIPAP) with face mask, have been effective in improving oxygenation and reducing hypercapnia 39 . Postoperative BIPAP has also been reported in conjunction with the laryngeal mask 40 .…”
Section: Anesthesia Planning and Perioperative Factors Associated Witmentioning
confidence: 91%
“…The LMA has been used for prolonged periods in adult intensive-care units (Arosio & Conci, 1995;Taylor & Bell, 1995), but there is no experience of prolonged LMA usage in the neonatal intensive-care unit. Theoretically, the LMA may be useful for short-term assistance during weaning because it can be used to provide continuous positive airway pressure or even inspiratory pressure support (Groudine, Lumb, & Sandison, 1995). Its use, however, depends on the patient having an empty stomach, a normal glottis, and compliant lungs.…”
Section: Neonatal Intensive-care Unitmentioning
confidence: 99%